Investigation of the effect of rock wool properties on the adsorption of nickel (II) from aqueous solutions - mohammad hadi abolhasani; niloofar pirestani; ali eslami (Mashhad University of Medical Sciences, 2021)
Abstract Background and Aim: Increasing levels of toxic heavy metals in the environment have led to risks to the health of humans and living organisms. Materials and methods: First, some characteristics of rock wool including pH, EC, pHZPC, chemical composition, structure, and morphology were determined using XRD, XRF, and Scanning Electron Microscopy (SEM). Adsorbing tests were then conducted in a non-continuous reactor using synthetic solutions containing nickel. Optimum adsorption conditions were determined concerning pH, metal initial concentration, contact time, and adsorbent dose. The data were analyzed in a completely randomized block design. Results: The highest adsorption was seen at pH = 5 and the lowest at pH = 3, with a significant difference. The absorption rate was significantly higher in the 5 mg/l solutions than in other concentrations and the lowest was observed at 100 mg/l concentration. The lowest nickel adsorption rate was observed in 5 min and the highest adsorption efficiency was observed in 90 min, with a significant difference. The adsorption percentage of rock wool waste at the 10 g/l doses was significantly higher than that in other adsorbent doses and the lowest adsorption percentage was observed at the 1 g/l dose. The isotherm studies showed that the adsorption of nickel by rock wool waste was consistent with the Freundlich model. Conclusion: It can be concluded that rock wool waste could remove nickel from industrial effluents.